Rural Electrification in the Changing paradigm of Power Sector Reforms in India - Gopalkrishna D Kamalapur; Udaykumar R Y (International Journal of Electrical and Computer Engineering (IJECE), 2012)
Rural electrification is an integral component of poverty alleviation and rural growth of a nation. In India, electricity has not played effective role in the socio-economic growth of village. GDP is increasing with 8 percent where as contribution of agriculture sector is 1.9 percent. Government of India has ambitious target of providing electricity to all villages by 2008 and all rural households by 2012. Steps are already initiated with Rural Electric Corporation, Rural Electricity Supply Technology mission, State Electricity Boards, Reforms in Power Sector. An attempt has been made in this paper to assess the features of rural electrification in India and the problems faced by State Electricity Boards. Challenges of rural electrification in the changing scenario of power sector reforms are identified.DOI:http://dx.doi.org/10.11591/ijece.v2i2.149